The Kumada-corriu cross-coupling reaction in micro reactor: Advantages over conventional batch reactor - Sơn Nam và cộng sự, Phan Thanh (Vietnam Journal of Chemistry, 2014)
A micro reactor has been used as an alternative to conventional batch reactors for the industrially important Kumada-Corriu cross-coupling reaction of 4-bromoanisole with phenylmagnesium chloride and phenylmagnesium bromide, in the presence of polymer- and silica-supported nickel catalysts. Reasonable conversions could be achieved in a matter of minutes, compared to conversions obtained after 24 h in a conventional batch reactor, albeit on a much smaller scale. The rate constant of the cross-coupling reaction could be increased up to 75 times using the micro reactor, as compared to the batch reaction. The deposition of magnesium species on the surface of the nickel silica catalyst still remains to be solved, while the problem is considerably less serious for the nickel resin catalyst used in the micro reactor system.